2005
DOI: 10.1039/b504210k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3,4-dihydro-2H-pyrans by hetero-Diels–Alder reactions of functionalized α,β-unsaturated carbonyl compounds with N-vinyl-2-oxazolidinone

Abstract: Cycloadditions of 3-aryl-2-benzoyl-2-propenenitriles and 3-phenylsulfonyl-3-buten-2-one to N-vinyl-2-oxazolidinone proceed regio- and diastereoselectively yielding cis and trans diastereoisomers of 4-aryl-3,4-dihydro-2-(2-oxo-3-oxazolidinyl)-2H-pyrans in 37-65% yield. Cycloadducts cis- were the major products. Reaction of 5-arylidene-1,3-dimethylbarbituric acids with dienophile afforded mixtures of 2H-pyrano[2,3-d]pyrimidine-2,4(3H)-diones trans and products resulted from an elimination of 2-oxazolidinone, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The scope of intermolecular HDA reactions of 1-oxa-1,3-butadienes with inverse-electron-demand was expanded to cycloadditions with enecarbamate [78]. Cycloadditions of 3-aryl-2-benzoylprop-2-enenitriles and 3-phenylsulfonylbut-3-en-2-ones 25 to N -vinyl-2-oxazolidinone 26 proceeded regio- and diastereoselectively, yielding cis 27 and trans 28 diastereoisomers of 3,4-dihydro-2-(2-oxo-3-oxazolidinyl)-2 H -pyrans in 37–65 % yield (Scheme 5).…”
Section: Inverse-electron-demand Hetero-diels–alder Reactions Of 1-oxmentioning
confidence: 99%
“…The scope of intermolecular HDA reactions of 1-oxa-1,3-butadienes with inverse-electron-demand was expanded to cycloadditions with enecarbamate [78]. Cycloadditions of 3-aryl-2-benzoylprop-2-enenitriles and 3-phenylsulfonylbut-3-en-2-ones 25 to N -vinyl-2-oxazolidinone 26 proceeded regio- and diastereoselectively, yielding cis 27 and trans 28 diastereoisomers of 3,4-dihydro-2-(2-oxo-3-oxazolidinyl)-2 H -pyrans in 37–65 % yield (Scheme 5).…”
Section: Inverse-electron-demand Hetero-diels–alder Reactions Of 1-oxmentioning
confidence: 99%
“…The only products and C-7 of the dihydropyran ring in the 1 H NMR spectra ( Figure 2, Table 9). In previous papers, 22,23 it was shown that reactions 5-arylidene-N,N-dimethylbarbituric acids with styrenes or N-vinyl-2-oxazolidinone required refluxing in toluene for 24-36 hours for styrenes 22 and 3-5 hours for N-vinyl-2-oxazolidinone. 23 The reactions performed 'on water' in heterogeneous phase were faster (1-3 h) than those executed in refluxing toluene solution.…”
Section: Figurementioning
confidence: 99%
“…In previous papers, 22,23 it was shown that reactions 5-arylidene-N,N-dimethylbarbituric acids with styrenes or N-vinyl-2-oxazolidinone required refluxing in toluene for 24-36 hours for styrenes 22 and 3-5 hours for N-vinyl-2-oxazolidinone. 23 The reactions performed 'on water' in heterogeneous phase were faster (1-3 h) than those executed in refluxing toluene solution. The 'on-water' reactions were characterized by very high endo/exo diastereoselectivity in contrast to reactions in boiling toluene for which a cis/trans diastereoselectivity of 1:1 was observed.…”
Section: Figurementioning
confidence: 99%
“…Pyranes and cyclic ketones are biologically active compounds to make up a structural part of natural compounds [1][2]. New [4+2] annulations were carried out in the presence of triphenylphosphine catalyst and high yield synthesized functionalized dihydropyranes [3].…”
Section: Introductionmentioning
confidence: 99%